The translation of πνευμα in John 3:8 - Potgieter, Annette (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
All Afrikaans translations of John 3:8 translates πνευμα as “wind”. A progression of the meaning of the word πνευμα is evident considering the background of πνευμα in Greek and Jewish thought. This progression is helpful in discerning viable translations of John 3:8, especially in Afrikaans translations. A variation of the Afrikaans translation of “wind” to “spirit” in John 3:8 can be helpful to broaden our understanding.